Musculoskeletal Pain of Gastrointestinal Endoscopists (International Journal of Occupational Safety and Health, 2025)
Introduction: Prolonged and repetitive musculoskeletal injuries are common among gastroenterologists who are overwhelmed with complex endoscopic procedures. Data is sparse regarding procedure-related musculoskeletal pain among endoscopists in Bangladesh. The objective of the study was to find out the frequency, sites, severity and factors related to musculoskeletal pain of practicing GI endoscopists in Bangladesh.Methods: This cross-sectional study was conducted using Google Forms (a pre-designed structured questionnaire) among 91 Gastrointestinal Endoscopists of different gastroenterology centers of Bangladesh from 1st October 2021 to 30th June 2022. Data were collected using the total population sampling technique.Results: The average weekly duration of doing endoscopic procedures was 8.1 ± 7.7 hours (median 5 hours).  More than half (52.7%) of the endoscopists had musculoskeletal pain. The most painful site was the low back. On average, the severity of pain on a numerical rating scale is 3. 92 ± 1.74 out of 10. Musculoskeletal pain was significantly more common among endoscopists with more average weekly procedures (p = 0.029).Conclusion: Musculoskeletal pain is frequent among endoscopists in Bangladesh. Reducing the number of procedures may help to some extent in this regard.